Pengaruh Permainan Puzzle terhadap Kemampuan Beradaptasi Sosial Siswa Retardasi Mental - Dwi Wulandari; Nelvia Nelvia; Dwi Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of puzzle play social adaptation on mental retardation students in SDLB Dharma Wanita Bengkulu City. The research design used was pre-experimental design with the design of one group pretest-posttest design. The results showed that the average number of children who experienced mental retardation before the puzzle game had unfavorable social adaptations and the average number of children who experienced mental retardation after doing the puzzle game had a fairly good social adaptation and there was no effect between playing technical skills. puzzle. For social adaptation of students with mental retardation in Dharma Wanita SDLB in the city of Bengkulu (p = 0.004). In conclusion, there is an influence between playing puzzle on the ability to adapt socially to mental retardation students at SDLB Dharma Wanita Bengkulu City. Keywords: Social Adaptation, Puzzle Games, Mental Retardation